Análise química de metabólitos voláteis das folhas de Psidium cattleyanum - Machado, Felipe Eduardo Rocha (2023)
Essential oils are fat-soluble substances, however volatile comprising the secondary metabolism of plants. Since they are a mixture of various organic compounds, essential oils have extensive applicability in the pharmaceutical, cosmetic and food industries. Psidium cattleyanumis have phenolic compounds such as anthocyanins and flavonoids are found in the skin of fruit and have antioxidant activity. Moreover, the red Psidium cattleyanum possess high vitamin C content and β-Cryptoxanthin Carotenoid which converts to vitamin A, which can be used to reduces the risk of degenerative diseases, prevention of cataracts, reduction of macular degeneration caused by aging and reduction of coronary heart diseases. The objective of this study is to determine the chemical composition of the essential oil of plant Psidium cattleyanum and seasonal assessment of essential oil composition. For the extraction of essential oil, the hydrodistillation technique is being used. The plant material is dried at 50ºC per 48 hours in an oven. Afterwards, the material was triturated in a blander blade and deposited in a 1 L round-bottomed flask. After the addition of 600 mL of distilled water, the flask was connected to a modified Clevenger system and heated to boiling water temperature. Because it has a higher vapor tension than water, the essential oil is swept with water’s vapor. After the extraction, the essential oil was subjected to a chromatography analysis at GC-MS (Gas Chromatography coupled with Mass Spectrometry) for the component’s characterization. The highest yield was in the month of July, presenting 0.28% ± 0.03% and the lowest yield was in the month of August 2021 with 0.11% ± 0.06%. In the chromatograms acquired, it was possible to observe that the compounds α- tujene, 1,8-Cineole, β-Caryophyllene, α-Humulene, α-Selinene and β-Selinene showed the highest proportion among the other compounds arranged in the essential oil. In relation to the climate, it was found that some compounds such as 1,8-Cineole and α-Humulene showed sensibility to climate variations, modifying their concentration in essential oil. In the other hand, the compounds α-Selinene and β- Selinene have not showed significative variations on their concentrations during the study, indicating low climatic influence or similar effect on both. The biological assays, of the essential oil extracted from the leaves of Psidium cattleyanum, in relation to antimicrobial activity, demonstrated inhibitory potential against the species Bacillus cereus, Pseudomonas aeruginosa, Staphylococcus aureus, Enterococcus faecalis, Bacillus thiringiensis, Paeni bacillus, Escherichia coli, in tests using concentrations of 10%, 20% and the pure essential oil, being possible to observe small halos, in the concentrations of 20% and pure, against some species.